PENGARUH ABU TULANG SAPI SEBAGAI BAHAN TAMBAH AGREGAT HALUS DALAM PEMBUATAN BETON READY MIX - Satria Agung Wibawa (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2023)
ABSTRACT In this study the authors aimed to determine the effect of using beef bone aggregate as an added ingredient for sand (fine aggregate) as well as an added ingredient for making ready mix concrete. The percentage levels of beef bones used in this study were 4%, 6% and 17%. In the manufacture of the test object is done by mixing the binder (cement), sand (fine aggregate and cow bone ash), gravel (coarse aggregate) and water using the experimental method. Samples of specimens were made using cylindrical molds (molds) and treated. The concrete compression test was carried out using a press machine, the mix design plan for making concrete was planned at 30 MPa. The total test objects made in this study were 20 pieces. The results of the test object with a cow bone ash content of 4% obtained compressive strength results of 7.58MPa 8.775 MPa 11.21 MPa 10.92 MPa and 10 MPa with an average value of 9.7 MPa. From the results of the addition of 6% beef bone ash, the results were 9.79 MPa, 9.73 MPa, 8.03 MPa, 9.23 MPa and 13.36 MPa and an average value of 10 MPa, for results with an addition of 17% cow bone ash was 10.3 MPa, 18.11 MPa, 15.28 MPa, 16.53 MPa and 19.13 MPa with an average yield of 15.87 MPa Keyword: Concrete, Cow Bone Ash, Compresive masive, Aggregate.